2015
DOI: 10.1080/0031322x.2015.1024404
|View full text |Cite
|
Sign up to set email alerts
|

Gendering the vote for populist radical-right parties

Abstract: Why do more men than women vote for populist radical-right (PRR) parties? And do more men than women still vote for the PRR? Can attitudes regarding gender and gender equality explain these differences (if they exist)? These are the questions that Spierings and Zaslove explore in this article. They begin with an analysis of men's and women's voting patterns for PRR parties in seven countries, comparing these results with voting for mainstream (left-wing and right-wing) parties. They then examine the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 7 publications
1
85
2
4
Order By: Relevance
“…For instance, the aforementioned authors positioned their work in the Netherlands, a country known to be one of the more sexually tolerant countries, but Western countries actually display quite a strong variation in the granting of rights to and political discourses around sexual minorities (Van den Akker, Van der Ploeg, and Scheepers 2013). In their study on voting PRR, Spierings and Zaslove (2015a) only found hints of this mechanism for some of the countries included.…”
Section: Shifting Party Positions On Sexualitymentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, the aforementioned authors positioned their work in the Netherlands, a country known to be one of the more sexually tolerant countries, but Western countries actually display quite a strong variation in the granting of rights to and political discourses around sexual minorities (Van den Akker, Van der Ploeg, and Scheepers 2013). In their study on voting PRR, Spierings and Zaslove (2015a) only found hints of this mechanism for some of the countries included.…”
Section: Shifting Party Positions On Sexualitymentioning
confidence: 99%
“…Perceiving migrants as possessing conflicting sexual norms could then actually be at the heart of anti-immigrant attitudes. Empirically, this is, for instance, reflected in the reinforcing impact of liberal sexual norms and anti-migration attitudes on voting for populist radical right in Norway and Sweden (Spierings and Zaslove 2015a).…”
Section: Cultural Threat: Anti-migration and Attitudes Towards Homosementioning
confidence: 99%
See 3 more Smart Citations